2017
DOI: 10.3390/mi8120354
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Circular Micro-Platform with Integrated Waveguides and Latching Arm for Reconfigurable Integrated Optics

Abstract: This work presents a laterally rotating micromachined platform integrated under optical waveguides to control the in-plane propagation direction of light within a die to select one of multiple outputs. The platform is designed to exhibit low constant optical losses throughout the motion range and is actuated electrostatically using an optimized circular comb drive. An angular motion of ±9.5° using 180 V is demonstrated. To minimize the optical losses between the moving and fixed parts, a gap-closing mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Unlike the MEMS-actuated switches in Figure 4a,b, these devices operate with a low-voltage comb electrostatic actuator. Recently, Briere et al reported a MEMS-actuated switches based on the laterally rotating comb actuators (Figure 4e,f) [67]. The light turns on when the fixed port is aligned with one of the rotational ports.…”
Section: Silicon Photonic Waveguide Switch Enginesmentioning
confidence: 99%
“…Unlike the MEMS-actuated switches in Figure 4a,b, these devices operate with a low-voltage comb electrostatic actuator. Recently, Briere et al reported a MEMS-actuated switches based on the laterally rotating comb actuators (Figure 4e,f) [67]. The light turns on when the fixed port is aligned with one of the rotational ports.…”
Section: Silicon Photonic Waveguide Switch Enginesmentioning
confidence: 99%
“…Previous devices developed by our research group relied upon a rotational MEMS platform for planar optical switching using SiN waveguides surrounded by a SiO 2 cladding [42]. The device uses 5° of its total 9.5° of rotation on each side to form a crossbar switch requiring 113 V to actuate and having a 1.3 mm by 1 mm footprint.…”
Section: Design Considerationsmentioning
confidence: 99%
“…The longitudinal motion of the central platform is unidirectional and designed to completely close the air gap between waveguides on the substrate and the platform to achieve highly efficient butt-coupling. The design operates at a reduced actuation voltage for both switching and gap closing motions compared to that reported in [42], and the device footprint is smaller. Figure 1 shows illustrations for the translational MEMS platform as a 1 × 3 optical switch (Figure 1a) and as a 2 × 2 crossbar optical switch (Figure 1b).…”
Section: Design Considerationsmentioning
confidence: 99%
See 2 more Smart Citations